The Role of Waste Pickers' Cooperatives and the Partnership with the Government: case study in the Maceió Urban Waste Recyclers Cooperative - COOPLUM/O Papel das Cooperativas dos Catadores e a Parceria com o Poder Público: estudo de caso na Cooperativa de Recicladores de Lixo Urbano de Maceió - COOPLUM - Elder Henrique Silva Rodrigues de Melo; Conceição Maria Dias de Lima (Universidade Estadual de Alagoas, 2020)
The article showed the role of recycling cooperatives in Alagoas, having as object of case study the Cooperative of Urban Waste Recyclers of Maceió - COOPLUM. The study starts from a literature review and document analysis. In this work, you will have an important role of this cooperative in the process of disposal, conscious disposal and recycling of part of the waste consumed in Maceió.